Diagnosis and treatment of brain compression in children with hemostasis disorders - M. L. Lagunavichene; S. N. Larionov; Y. A. Aleksandrov; A. V. Livadarov; P. G. Gruzin; A. V. Rudakova; E. G. Osipova (Русский журнал детской неврологии)
We describe the diagnosis of and treatment for brain compression on background of hemostasis disorders in 6 out of 37 patients with hemorrhagic strokes treated in the Ivano-Matreninskaya Children’s Clinical Hospital in 2017–2018. Laboratory examination revealed factor VIII deficiency (hemophilia A) in 3 patients, factor XIII deficiency in one patient; 2 children were carriers of thrombophilia genetic polymorphisms. The age of study participants varied between 15 days and 2 years; all of them were males. They have undergone neurological examination, laboratory testing (hemostasis), neurosonography, multislice computed tomography, and magnetic resonance imaging. Conservative therapy with quarantined fresh frozen plasma (15–25 mL/kg) was used to correct coagulopathy and stop bleeding. Two patients had surgeries: decompressive craniectomy and drainage and endoscopic removal of hematoma. Children that were operated on received transfusion of fresh frozen plasma and red blood cells. Both of them had regression of neurological symptoms and restoration of consciousness in the postoperative period. None of the patients died. In this article, we discuss diagnostics and strategy of conservative and surgical treatment for children with brain compression and coagulopathies.